Progressive Prosecution : Race and Reform in Criminal Justice - Thompson, Anthony C.; Taylor-Thompson, Kim (Book collections on Project MUSE., 2022)
"The 2020 murder of George Floyd rocked nearly every aspect of American life and brought issues of police brutality to the forefront of public discourse. In the wake of his death and under extreme public pressure, many politicians, police chiefs, and court officials acknowledged the existence of systemic inequality in the fields of policing and criminal justice. However, with few exceptions, one actor within the justice system remained painfully silent: prosecutors. Progressive Prosecution both argues that this group should be at the forefront of calls for criminal justice reform and provides a guidebook for how this can be achieved. To date, little has been written that offers real guidance to District Attorneys and their staffs to help them shape a new culture within their offices dedicated to race-conscious practices and even-handed approaches. And even less has been written to educate a broader audience about the importance of a race-sensitive, community-based prosecution function in making real change in the criminal justice system and moving toward real justice. Progressive Prosecution offers both through a curated collection of chapters written by criminal justice experts and practicing District Attorneys focused on those components of prosecution policy and practice that deserve and demand radical rethinking. The book puts forth a radical new vision of prosecution: prosecutors must redefine the future of the criminal justice system"--